Gender differences in substance use and associated factors among urban refugees in Uganda - Bahati, Ronald; Ashaba, Scholastic; Sigmund, Cathy Denise; Rukundo, Godfrey Zari; Ainamani, Herbert Elvis (Informa UK Limited, 2023)
Background: Alcohol and other substances use related problems among refugees is a global public health concern. Although there is substantial research on the use of alcohol and other substances among the refugees, little is known about gender and other factors that might be associated with the use of alcohol and other substances. Our study aimed to assess the prevalence of alcohol and substance use across gender and other specific associated factors among urban refugees living in Mbarara city, Southwestern Uganda. Methods: In a cross-sectional study, 343 refugees were interviewed on the use of alcohol and other substances using the Alcohol Use Disorder Identification Test and the Drug Abuse Screening Test. The associated factors included, age, marital status, occupation, duration (length of stay) in Uganda, educational levels, stigma and depression. Linear regression analysis was used to examine the associations between the predictor and outcome variables. Results: No significant gender difference in alcohol use was found, and the overall prevalence of hazardous, harmful or dependent alcohol use among our sample of refugees living in Mbarara city was 43%. There were however, statistically significant gender differences in the use of other substances, with a significantly higher percentage of men than women reporting intermediate, substantial, or severe substance use (45% among men, 37% among women). Higher levels of depression and being separated from one’s spouse were associated with higher levels of alcohol and substance use. In addition, higher age and being male were associated with the use of substances other than alcohol. Conclusions: Our findings indicate a high prevalence of problematic alcohol and substance use among both male and female refugees. Clinical interventions focused on the treatment and prevention of alcohol and substance use among the refugee communities may benefit from focusing on depressive symptoms as well.